Desmoplastic Fibroma-A Rare Case Report - Nithya, S (J Oral Maxillofac Pathol, 2015)
Desmoplastic fibroma (DF) is a benign intra-osseous neoplasm, that is, recognized as the intra-osseous counterpart of soft tissue fibromatosis in both gnathic and extra-gnathic sites. It has a propensity for locally aggressive behavior and local recurrence. An occurrence of intra-osseous lesion other than that of odontogenic origin is rare in the jaws. In this case report, we define the clinico-pathological and radiographic features of DF of the mandible in a 35-year-old female, who presented to the Outpatient Department with a 3-year history of a slowly expanding painless mass in the left mandibular posterior region. Thus, we present a classic case of DF exhibiting characteristic features along with a review of the literature.